Alleviation of Cadmium Toxicity in Rice by γ-Polyglutamic Acid Produced by Bacillus subtilis - Nuchnapa Kotabin; Kritchaya Issakul; Elke Pawelzik; Yasutaka Tahara; Orawan Chunhachart (EnvironmentAsia, 2017)
The effect of γ-polyglutamic acid (PGA) produced by Bacillus subtilis on cadmium (Cd)-damaged rice was investigated in experiments with pots containing soil contaminated with Cd at a concentration of 0-200 mg/kg and PGA at a concentration of 0-500 mg/kg. Although Cd reduced the growth and productivity of rice in comparison to the control, the addition of 500 mg/kg of PGA alleviated the effects of Cd toxicity in rice, resulting in increases in shoot and root lengths, the vigor of the rice and the number of seeds per panicle. Micrographs of ultrathin sections of root cells showed that the addition of 500 mg/kg of PGA decreased Cd accumulation in both the epidermis and the intracellular space of cortex, suggesting that PGA reduced Cd transportation into root cells. Based on these results and the metal-binding characteristics of PGA, it is conceivable that the mechanism by which PGA alleviates Cd toxicity is the extracellular formation of Cd-PGA complexes.